Gus Iqdam’s Dakwah Bil Hikmah through the Sabilu Taubah Assembly - Ach Wahidi Wahidi; Baidawi (Fakultas Dakwah UIN Kiai Haji Achmad Siddiq Jember, 2024)
This article explores Gus Iqdam’s Dakwah Bil Hikmah through the Sabilu Taubah Assembly, in light of the increasing prominence of majelis taklim (religious study assemblies), particularly in their methods, strategies, and use of media for dakwah (Islamic preaching). The Sabilu Taubah Assembly, led by Gus Iqdam, is notably popular among Nahdliyin communities. This study aims to analyze Gus Iqdam’s dakwah bil hikmah approach in uniting diverse groups through the Sabilu Taubah assembly. Utilizing a descriptive qualitative method, data collection techniques include observation, interviews, and documentation. Findings indicate that Gus Iqdam’s success in dakwah stems from his role as a preacher and mentor at the majelis taklim in Karanggayam Village, Srengat District, Blitar Regency. Gus Iqdam, also known as Agus Muhammad Iqdam, is a young preacher and leader within the Nahdlatul Ulama community. His dakwah work goes beyond delivering sermons, focusing on key elements essential for a successful dakwah practitioner, such as the rhetorical principles of ethos (hikmah), pathos (al-mau'idah hasanah), and logos ('al-Jidal billati hiya ahsan). This study aims to contribute to dakwah knowledge by reinforcing existing dakwah theories with its findings